Programming the composition of polymer blend particles for controlled immunity towards individual protein antigens. Issue 23 (28th May 2015) - Zhan, Xi; Shen, Hong
Graphical abstract: Abstract: In order for a more precise control over the quality and quantity of immune responses stimulated by synthetic particle-based vaccines, it is critical to control the colloidal stability of particles and the release of protein antigens in both extracellular space and intracellular compartments. Different proteins exhibit different sizes, charges and solubilities. This study focused on modulating the release and colloidal stability of proteins with varied isoelectric points. A polymer particle delivery platform made from the blend of three polymers, poly(lactic- co -glycolic acid) (PLGA) and two random pH-sensitive copolymers, were developed. Our study demonstrated its programmability with respective to individual proteins. We showed the colloidal stability of particles at neutral environment and the release of each individual protein at different pH environments were dependent on the ratio of two charge polymers. Subsequently, two antigenic proteins, ovalbumin (OVA) and Type 2 Herpes Simplex Virus (HSV-2) glycoprotein D (gD) protein, were incorporated into particles with systematically varied compositions. We demonstrated that the level of in vitro CD8 + T cell and in vivo immune responses were dependent on the ratio of two charged polymers, which correlated well with the release of proteins. This study provided a promising design framework of pH-responsive synthetic vaccines for protein antigens of interest.